Ecopedagogia e pedagogia do sentido: diálogos possíveis - (:unkn) unknown (Universidade Brasil, 2021)
The present work has as main objective to contribute with the accomplishment of a critical Environmental Education, for students and teachers of High School, through the studies of Logotherapy / Logoeducation. The research has a qualitative approach and was carried out with a literature review. This was based on works by the creator of Logotherapy, Viktor Frankl, authors who relate it to Education, as well as authors who support Ecopedagogy and critical Environmental Education. It was concluded that the concepts of Logotherapy / Logoeducation can contribute to the process of change in education, through reflections on its main concepts; furthermore, it could be concluded that the literature presents itself as a rich source for the development of strategies within logoeducation that can promote significant changes in human behavior based on critical reflection on reality.As a product of the research, a paradidactic book was created that can help the teacher to promote discussions and reflections that collaborate with the integral formation of these young people.
Keywords: Educação ambiental; Logoeducação; Ecopedagogia; Pedagogia do sentido; Abordagem interdisciplinar; CB